Analisis Perbandingan Kinerja Keuangan Sebelum dan Sesudah Akuisisi pada PT Solusi Bangun Indonesia Tbk - Wildan Drajat Wibowo; Sri Murwanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to find out the differences in the financial performance of PT Solusi Bangun Indonesia Tbk before and after it was acquired by PT Semen Indonesia Tbk in 2019. The focus of the analysis includes the Return on Equity (ROE), Return on Assets (ROA), Current Ratio (CR) ratio, Quick Ratio (QR), Total Assets Turn Over (TATO), ang Debt to Equity Ratio (DER). Researchers used a quantitative approach through the use of secondary data based on financial reporting at PT Solusi Bangun Indonesia Tbk over a period of 5 years before (2014-2018) and 5 years after (2019-2023) it was acquired. This sampling used purposive sampling technique. The data was analyzed using the Kolmogorov-Smirnov normality test and parametric difference test (paired sample t-test) and non-parametric difference test (Wilcoxon test) using SPSS software. The analysis shows that there is no significant difference in ROA with ROE, DER and TATO before and after acquisition. However, significant differences in CR and QR were found after the acquisition, indicating an increase in the company's liquidity.